(untitled) (Revista Científica Integrada, 2025)
Objective: To map whether women undergoing tubal ligation experience increased vaginal bleeding during the menstrual period. Method: Scoping review conducted according to the Joanna Briggs Institute (JBI) guidelines, based on the PICO strategy: P (population) – women of reproductive age who underwent tubal ligation; I (intervention) – implementation of different tubal sterilization techniques; C (comparison) – women without ligation or who underwent alternative techniques; and O (outcome) – changes in menstrual bleeding pattern. The search was conducted in October 2025 in the PubMed/MEDLINE, Scopus, Web of Science, and Virtual Health Library (VHL) databases, using controlled descriptors and free terms in Portuguese, English, and Spanish. Studies published between 2015 and 2025 were included. Results: Of the 224 records initially identified, nine studies met the eligibility criteria. Most studies, mainly retrospective and prospective cohorts, were conducted in countries such as Iran, the United States, Turkey, Pakistan, and India. Although some studies (Iran, 2016; Pakistan, 2020) reported a significant increase in menorrhagia (≈63–67% vs. 22–23% in controls), large U.S. cohorts and Turkish investigations did not observe a significant increase in bleeding after ligation. Overall, findings indicate that increased menstrual bleeding is not universal and appears to depend on factors such as surgical technique, previous menstrual history, and hormonal profile. Conclusion: The relationship between tubal ligation and increased uterine bleeding remains controversial and multifactorial. Evidence suggests that potential menstrual changes result more from individual and gynecological factors than from the procedure itself.